Detention of Incapacitated Patients by Hospitals as a Violation of Constitutional Rights in Health Services - Wiweka, Wiweka; Barthos, Megawati (International Journal of Social Service and Research, 2025)
Detention of patients in hospitals for inability to pay is a practice that is contrary to the principles of human rights and social justice. This practice not only violates the right to individual liberty as stipulated in Article 28G paragraph (1) and Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia, but also contradicts the mandate of Article 189 paragraph (1) letter f of Law Number 17 of 2023 concerning Health which requires hospitals to carry out social functions by providing services to underprivileged patients. This research aims to examine the applicable legal arrangements, evaluate the implementation of the social function of hospitals, and formulate fair and proportionate legal reforms in the face of the reality of patient detention. Using empirical juridical approaches and qualitative methods, data were collected through literature studies and interviews with relevant parties. The results of the study show that there is an imbalance between the hospital's obligation to carry out social functions and the hospital's institutional needs to cover operational costs. Unclear financing mechanisms for underprivileged patients, weak coordination between government agencies, and suboptimal regulatory supervision lead to violations of patients' rights. Therefore, comprehensive legal reform is needed by emphasizing the state's obligation to ensure health services without discrimination, as well as developing a financing mechanism that ensures the sustainability of hospitals. The reformulation of legal norms in the Health Law and its derivative apparatus must be based on the principles of social justice and the state's responsibility for the right to health, so that the law truly protects the basic rights of citizens while maintaining the balance of the health service system